Interbank asset-liability networks with fire sale management - Zachary Feinstein; Grzegorz Ha±aj (European Central Bank (ECB), 2023)
Interconnectedness is an inherent feature of the modern financial system. While it contributes to efficiency of financial services, it also creates structural vulnerabilities: pernicious shock transmission and amplification impacting banks' capitalization. This has recently been seen during the Global Financial Crisis. Post-crisis reforms addressed many of the causes of this event, but contagion effects may not be fully eliminated. One reason for this may be related to financial institutions' incentives and strategic behaviours. We propose a model to study contagion effects in a banking system capturing network effects of direct exposures and indirect effects of market behaviour that may impact asset valuation. By doing so, we can embed a well-established fire-sale channel into our model. Unlike in related literature, we relax the assumption that there is an exogenous pecking order of how banks would sell their assets. Instead, banks act rationally in our model; they optimally construct a portfolio subject to budget constraints so as to raise cash to satisfy creditors (interbank and external). We assume that the guiding principle for banks is to maximize risk-adjusted returns generated by their balance sheets. We parameterize the theoretical model with publicly available data for a representative sample of European banks; this allows us to run simulations of bank valuations and asset prices under a set of stress scenarios.
Keywords: C62; C63; G11; G21; 330; systemic risk; interbank contagion; fire sales; optimal portfolio